Penyuluhan Pengolahan Jeruk Lemon dan Keripik Kentang bagi UMKM, Pokdarwis, Petani, Nelayan, Kader Posyandu, dan Peternak pada Desa Wisata Margaluyu Pengalengan, Kabupaten Bandung - Novyarni, Nelli; Harni, Reni; Kartijo (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This activity aims to provide education on proper techniques for processing lemons and potato chips, specifically for MSMEs, Pokdarwis, farmers, fishermen, posyandu cadres, and livestock breeders in the tourist village of Margaluyu, Pengalengan, Bandung district. The method employed in this activity involves counseling based on materials provided by competent resource persons. The results of this community service activity indicate that participants have gained a clear understanding of the importance of proper processing techniques, as well as the economic impacts on MSMEs, Pokdarwis, farmers, fishermen, posyandu cadres, and breeders in Margaluyu Tourism Village, Pengalengan, Bandung Regency. Additionally, participants have also improved their skills in financial management